Aligning Prosecutorial Responsibility and Authority: Strengthening the Dominus Litis Principle in Indonesia - Mayhardy Indra Putra; Adwani Adwani; Riza Nizarli; Joelman Subsidi (SCAD Independent, 2026)
Despite the formal recognition of the dominus litis principle, weak prosecutorial control over investigations continues to undermine legal certainty in Indonesia’s criminal justice system. Existing studies largely focus on prosecutorial discretion and restorative justice, leaving the relationship between prosecutorial responsibility, authority, and investigative accountability underexplored. This study examines the juridical implications of limited supplementary investigation authority and its consequences for the effective implementation of the dominus litis principle. Employing a normative juridical approach, the study analyzes statutory regulations, legal doctrines, judicial interpretations, and relevant scholarly literature concerning prosecutorial authority and criminal justice governance. The findings indicate that the ineffective implementation of dominus litis originates from a structural misalignment between prosecutorial responsibility and authority, reinforced by normative weaknesses in Articles 109 and 110 of the Indonesian Criminal Procedure Code (KUHAP). By advancing a responsibility–authority alignment perspective, this study reframes supplementary investigation authority as an institutional mechanism for strengthening accountability, legal certainty, and effective criminal justice governance.